Psychological wellbeing among international students in Universiti Putra Malaysia during the pandemic - Che Man, Hasfalina; Talib, Zainal Abidin; Sulaiman, Abdul Hadi; Abdul Rahman, Suhaimi; Abdullah, Haslinda; Baharudin, Mohd Rafee; Ab Aziz, Izzah Farhana (Universiti Teknologi MARA (UiTM) Cawangan Pahang, 2023)
This study aimed to investigate the prevalence of physiological well-being among UniversitiPutra Malaysia (UPM) international students due to the lockdown during the COVID-19 pandemic and identify the determinants of depression and anxiety. A total of 411 international university students at UPM participated in this online-based survey. A standardized e-questionnaire was generated using Google Forms, and the link was shared through social media, e.g., WhatsApp, and thru students’ e-mails. The information was statistically analyzed by SPSS. Students experienced moderate depression and anxiety. The university is expected to consider to fixing factors in reducing depression and anxiety among international university students.